2014
DOI: 10.1186/1479-5876-12-96
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteomic analysis of white blood cells from chikungunya fever patients of different severities

Abstract: BackgroundChikungunya fever (CHIKF) is a recently re-emerged mosquito transmitted viral disease caused by the chikungunya virus (CHIKV), an Alphavirus belonging to the family Togaviridae. Infection of humans with CHIKV can result in CHIKF of variable severity, although the factors mediating disease severity remain poorly defined.MethodsWhite blood cells were isolated from blood samples collected during the 2009-2010 CHIKF outbreak in Thailand. Clinical presentation and viral load data were used to classify sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…A total of 2 mg of the sub-10 kDa protein fraction were reduced with DTT, alkylated with Iodoacetamide, digested with trypsin and subjected to LC-MS/MS analysis exactly as described previously [27]. The resultant mass spectra were analyzed with the DeCyder MS Differential Analysis software and the MS/MS data were submitted for a database search using the Mascot software (Matrix Science, London, UK).…”
Section: Protein Extraction Maldi-tof and Lc-ms/ms Analysismentioning
confidence: 99%
“…A total of 2 mg of the sub-10 kDa protein fraction were reduced with DTT, alkylated with Iodoacetamide, digested with trypsin and subjected to LC-MS/MS analysis exactly as described previously [27]. The resultant mass spectra were analyzed with the DeCyder MS Differential Analysis software and the MS/MS data were submitted for a database search using the Mascot software (Matrix Science, London, UK).…”
Section: Protein Extraction Maldi-tof and Lc-ms/ms Analysismentioning
confidence: 99%
“…On the other hand, increased expression of NLRP3 in human patients was observed during infection with chikungunya virus (CHIKV) and elevated caspase-1 expression and IL-1β levels were highly predictive markers of severe disease in humans [63,64]. Dengue virus (DV) also activates the NLRP3 inflammasome in human platelets that were experimentally infected or in platelets isolated from DV infected patients and high platelet derived IL-1β levels caused increased permeability in an in vitro assay and were associated with increased vascular permeability in clinical cases [65].…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“… Studies are identified by the first name of the author and where required, the year (Thio ; Abere ; Dhanwani (2011) ; Dhanwani (2014) ; ; Fraisier ; Wikan ; Puttamallesh ) and the protein ID or accession number listed in the study is given. Where required the proteome (liver or brain) or technique (DIGE or iTRAQ) is also indicated.…”
Section: Chikungunya Virus Proteome Studies: the Proteinsmentioning
confidence: 99%